Faktor Risiko Penyakit Jantung Koroner pada Pasien Rawat Jalan di Rumah Sakit Badan Pengusahaan Kota Batam Tahun 2021 - Andi Ipaljri Saputra; Sudarsono Sudarsono; Falah Haikal (Universitas Batam, 2022)
Background : Coronary Heart Disease (CHD) or known as Coronary Artery Disease (CAD) is a disease with a long course of disease and atheroclerosis occurs along the blood vessels. When the arteries supplying the myocardium are impaired, the heart is unable a pump a certain amount of blood effectively to meet adequate blood perfusion to vital organs and peripheral tissues. This study aims to determine the risk factors for coronary heart disease in outpatient at RSBP in 2021. Methods : The research design is a descriptive epidemiological study using a cross sectional method. The number of samples was 334 cardiac polyclinic patients who were taken using simple random sampling. The type of data used in this research is secondary data. The tool used in this study is the medical record of outpatient cardiac polyclinic patients at the Batam Management Agency Hospital (RSBP) in 2021, data analysis using the chi-square test. Results : The result of the analysis were found to have coronary heart disease (60,2%). The risk of coronary heart disease is more dominant in total cholesterol (66,8%). There was no association between gender with coronary heart disease. There is a relationship between coronary heart disease with total cholesterol, P-value obtained is 0,000 (p<0,05). Conclusion : Based on the results of this study, it can be concluded that there is a relationship between age, total cholesterol, LDL cholesterol, HDL cholesterol, triglyceride levels, history of hypertension, dan history of diabetes mellitus wih coronary heart disease in outpatients cardiac polyclinic patients at RSBP Batam in 2021, and there is no the relationship between gender with coronary heart disease in outpatients cardiac polyclinic at RSBP Batam in 2021.